“Astropolitics” and weaponisation of space—Drawing past lessons to address space arms' escalation - Ancona, Francesco (Frontiers in Political Science, 2025)
Once a distant dream, today space is not only achievable, but has become the most important domain for both civilian and military purposes. Modern society and its economy have come to vitally rely on space assets for running crucial services, from financial transactions, weather forecasting, telecommunications to navigation. Military operations are also heavily reliant on space to provide intelligence gathering, surveillance and communication capabilities. Once one of the few domains of international cooperation, space has become increasingly competitive, congested and contested. As we are navigating through an increasingly complex geopolitical environment, space is undergoing a similar process. Unlike during the Cold War, today Earth's low orbit is comprised of a higher number of national and private actors engaged in strategic competition with each other. While the use of space in support of military operations is not a novel concept, we are nonetheless witnessing an evolution of space emerging as the critical domain upon which national security and other sectors heavily depend. As it was the case with nuclear weapons during the Cold War, this is translating into a race for national space programs to acquire strategic advantage by developing space and counter-space systems. The objective of this paper is to draw a comparison between the militarization of space and the historical Cold War arms races, drawing lessons from that era and subsequent arms control frameworks. While accounting for space-unique challenges posed by a rapidly diversifying mix of state and private actors, the dual-use nature of modern space technologies, and the inherent difficulties in distinguishing between peaceful and hostile activities in orbit, as well as geopolitical considerations, this study highlights how measures from these past frameworks can be nonetheless emulated and implemented into currently available space diplomatic frameworks in order to mitigate risks, reduce misunderstandings, increase certainty, trust and accountability in space.